Antiaromaticity Gain Activates Tropone and Nonbenzenoid Aromatics as Normal-Electron-Demand Diels–Alder Dienes - Karas, Lucas J; Campbell, Adam T; Alabugin, Igor V; Wu, Judy I (Organic letters, 2020)
We propose a carbonyl umpolung strategy for activating tropone as a normal-electron-demand Diels–Alder diene. Tropone has low reactivity for Diels–Alder reactions because of its [4n+2] π-aromaticity. Conversion of the carbonyl group into a hydrazone ion (N–NR–) reverses the polarity of the exocyclic double bond, increases the [4n] ring π-antiaromaticity, and raises the HOMO energy. Computed gas-phase activation free energies for a Diels–Alder reaction with maleimide suggest a billion-fold rate increase when the tropone CO is replaced by N–NR– (R = H or SO2CH3). Other nonbenzenoid aromatics can be activated as normal-electron-demand Diels–Alder dienes in the same way.